Insertion of microneedles into skin: measurement and prediction of insertion force and needle fracture force - Davis, Shawn P; Landis, Benjamin J; Adams, Zachary H; Allen, Mark G; Prausnitz, Mark R (Journal of biomechanics, 2004)
As a hybrid between a hypodermic needle and transdermal patch, we have used microfabrication technology to make arrays of micron-scale needles that transport drugs and other compounds across the skin without causing pain. However, not all microneedle geometries are able to insert into skin at reasonable forces and without breaking. In this study, we experimentally measured and theoretically modeled two critical mechanical events associated with microneedles: the force required to insert microneedles into living skin and the force needles can withstand before fracturing. Over the range of microneedle geometries investigated, insertion force was found to vary linearly with the interfacial area of the needle tip. Measured insertion forces ranged from approximately 0.1–3 N, which is sufficiently low to permit insertion by hand. The force required to fracture microneedles was found to increase with increasing wall thickness, wall angle, and possibly tip radius, in agreement with finite element simulations and a thin shell analytical model. For almost all geometries considered, the margin of safety, or the ratio of fracture force to insertion force, was much greater than one and was found to increase with increasing wall thickness and decreasing tip radius. Together, these results provide the ability to predict insertion and fracture forces, which facilitates rational design of microneedles with robust mechanical properties.